2020
DOI: 10.1177/0887302x20917457
|View full text |Cite
|
Sign up to set email alerts
|

Fashion and the Buddha: What Buddhist Economics and Mindfulness Have to Offer Sustainable Consumption

Abstract: While consumers increasingly expect fashion companies to be bastions of social and environmental causes, they also aspire for fashion in ways known to erode human well-being, evidencing an ethics–behavior gap. The purpose of this conceptual article is to explore how Buddhist economics (BE) and mindfulness could narrow this gap; a spiritual consciousness making consumer ethics more consequential. Classical economic theory is contrasted with BE, a moral framework, including moderation and nonviolence. Mindfulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
0
11
1
1
Order By: Relevance
“…This contradicts the extant literature which mentioned that people who perceive nature as self and have high self-transcendence protect the environment to become one with God (Johnson et al, 2017;Perera and Hewege, 2018) or Culture and sustainable apparel consumption attain self-fulfillment (Fraj and Martinez, 2006;Pekkanen et al, 2018). Our findings also contradict with the findings of the recent studies which found that spirituality influences green purchase behavior (Chairy and Syahrivar, 2020) and spiritual consciousness and mindfulness contribute to sustainable apparel consumption (Armstrong, 2021). Religious values are often externalized through rituals and rites whereas spiritual values are internalized as personal realizations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This contradicts the extant literature which mentioned that people who perceive nature as self and have high self-transcendence protect the environment to become one with God (Johnson et al, 2017;Perera and Hewege, 2018) or Culture and sustainable apparel consumption attain self-fulfillment (Fraj and Martinez, 2006;Pekkanen et al, 2018). Our findings also contradict with the findings of the recent studies which found that spirituality influences green purchase behavior (Chairy and Syahrivar, 2020) and spiritual consciousness and mindfulness contribute to sustainable apparel consumption (Armstrong, 2021). Religious values are often externalized through rituals and rites whereas spiritual values are internalized as personal realizations.…”
Section: Discussioncontrasting
confidence: 99%
“…the belief system that one's present deeds influence fate in the future) and spirituality influence green purchase behavior where spirituality mediates the relationship between karma and green purchase behavior. Armstrong (2021) suggested that spiritual consciousness and mindfulness could contribute to sustainable apparel consumption. Other studies by Elhoushy and Jang (2021) and Minton et al (2020) indicated that religiosity positively influences food waste reduction.…”
Section: How the Connection With Indigenous Cultural Values Influence...mentioning
confidence: 99%
“…The materialistic approach can adversely affect not only the well-being of an individual but also collective well-being. Buddhist Economics and mindfulness can help reduce the gap between intention and behaviour (Armstrong, 2021).…”
Section: Jibr 161mentioning
confidence: 99%
“…Thus, MC is a relatively new concept in comparison with mindfulness. Subsequently, many scholars opined that mindfulness had potential to influence MC behaviour (Armstrong, 2021; Bahl et al , 2016; Dhandra, 2019; Ericson et al , 2014; Gupta et al , 2021; Wamsler et al , 2018; Wang et al , 2023). However, the illustration of how mindfulness shapes mindset and translates it into consumption choices seems to be missing in most of these research papers.…”
Section: Introductionmentioning
confidence: 99%
“…Second, further research is called for in the context of Buddhism's impact on individuals' consumption patterns and behaviors (Armstrong, 2020;Gentina et al, 2021;Scherer & Waistell, 2019).…”
Section: Future Research Avenuesmentioning
confidence: 99%